2008
DOI: 10.1001/jama.300.6.676
|View full text |Cite
|
Sign up to set email alerts
|

Association of Combatant Status and Sexual Violence With Health and Mental Health Outcomes in Postconflict Liberia

Abstract: HE CONFLICT IN LIBERIA BEGAN in late 1989 when then−rebel leader Charles Taylor launched an incursion from neighboring Cote d'Ivoire. This conflict has been characterized by ethnic killings and massive abuses against the civilian population between 1989 and 1997 and again in 2003 and 2004. 1 Relative peace was established in 2004 and today, a fragile peace is maintained by the 15 000-strong United Nations Mission in Liberia troops 2 and a large international aid agency presence. The health, mental health, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
162
4
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(183 citation statements)
references
References 26 publications
13
162
4
4
Order By: Relevance
“…9 This exposure can include being forced to kill or harm others 1, 10 and repeated personal victimization, including sexual violence. 10 …”
Section: Introductionmentioning
confidence: 99%
“…9 This exposure can include being forced to kill or harm others 1, 10 and repeated personal victimization, including sexual violence. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Agger (1989) reported that 76% of male political prisoners in El Salvador had experienced at least one type of sexual torture during detention. The work of Kirsten Johnson (2008Johnson ( , 2010 has been particularly influential in drawing attention to issues of male CRSV. In Liberia, her team found that 32% of male ex-combatants had experienced sexual violence (10% less than the figure for female excombatants).…”
Section: Characterization Of Male-directed Sexual Violence In Conflictmentioning
confidence: 99%
“…More recently, researchers have sought to combine health surveys with crime victimization surveys developed in the field of criminology to also ask about perpetrators. 48,49,50,51 …”
Section: Estimating Mass Rape Using Hospital Records In the Former Yumentioning
confidence: 99%